Thermal stability of a eutectic mixture of bis(2, 2-dinitropropyl) acetal and formal: Part B. Degradation mechanisms under water and high humidity environments. (August 2016) - Yang, Dali; Pacheco, Robin; Edwards, Stephanie; Torres, Joseph; Henderson, Kevin; Sykora, Milan; Stark, Peter; Larson, Sheldon
Abstract: As a continuation of our effort to understand degradation mechanisms of a eutectic mixture of bis(2, 2-dinitropropyl) acetal (BDNPA) and bis(2, 2-dinitropropyl) formal (BDNPF) (referred to as NP) under various environmental conditions, we investigated the thermal stability of NP under water and 74% relative humidity (RH) environments at temperatures below 70 °C. Based on a comprehensive characterization of samples aged over a period of two years, we conclude that in the presence of water the reaction pathways of NP degradation are different from those observed in air or under nitrogen atmosphere. We found that the physical state of water molecules plays an important role as it determines the ability of oxygen to participate in the NP degradation process. Based on the results obtained in Parts A and B of these studies, we conclude that the rate of NP degradation increases in the following order: nitrogen < water < air < water vapor + air.